Determinants of inclusive economic growth in Latin America - Angulo-Bustinza, Harold (2023)
The work aims to identify the determinants that influence inclusive economic growth in Latin America. The study’s methodology is quantitative with a nonexperimental design, for whose effect analysis was developed through a panel data model to identify the determinant variables of inclusive economic growth. Annual data of the main macroeconomic and social variables were used for a sample of 14 Latin American countries (Argentina, Bolivia, Brazil, Chile, Colombia, Costa Rica, Ecuador, El Salvador, Honduras, Mexico, Panama, Paraguay, Peru, and Uruguay); the study horizon comprises 25 years, between 1995 and 2019. The following variables were found to have a direct influence on inclusive economic growth: public spending and international trade; the study also showed that inflation, unemployment, and the presence of crises have a negative impact on inclusive economic growth. Moreover, an additional public expenditure of 1% implies an increase of 0.100% in inclusive economic growth, and for each positive variation of 1% in international trade, inclusive economic growth responds with an increase of 0.144%.